Identification of Key Genes and Biological Pathways Associated with Skeletal Muscle Maturation and Hypertrophy in Bos taurus, Ovis aries, and Sus scrofa - Fatemeh Mohammadinejad; Mohammadreza Mohammadabadi; Zahra Roudbari; Tomasz Sadkowski (Animals, 2022)
The aim of the current study was to identify the major genes and pathways involved in the process of hypertrophy and skeletal muscle maturation that is common for Bos taurus, Ovis aries, and Sus scrofa species. Gene expression profiles related to Bos taurus, Ovis aries, and Sus scrofa muscle, with accession numbers GSE44030, GSE23563, and GSE38518, respectively, were downloaded from the GEO database. Differentially expressed genes (DEGs) were screened out using the Limma package of R software. Genes with Fold Change > 2 and an adjusted p-value < 0.05 were identified as significantly different between two treatments in each species. Subsequently, gene ontology and pathway enrichment analyses were performed. Moreover, hub genes were detected by creating a protein–protein interaction network (PPI). The results of the analysis in Bos taurus showed that in the period of 280 dpc–3-months old, a total of 1839 genes showed a significant difference. In Ovis aries, however, during the period of 135dpc–2-months old, a total of 486 genes were significantly different. Additionally, in the 91 dpc–adult period, a total of 2949 genes were significantly different in Sus scrofa. The results of the KEGG pathway enrichment analysis and GO function annotation in each species separately revealed that in Bos taurus, DEGs were mainly enriched through skeletal muscle fiber development and skeletal muscle contraction, and the positive regulation of fibroblast proliferation, positive regulation of skeletal muscle fiber development, PPAR signaling pathway, and HIF-1 signaling pathway. In Ovis aries, DEGs were mainly enriched through regulating cell growth, skeletal muscle fiber development, the positive regulation of fibroblast proliferation, skeletal muscle cell differentiation, and the PI3K-Akt signaling, HIF-1 signaling, and Rap1 signaling pathways. In Sus scrofa, DEGs were mainly enriched through regulating striated muscle tissue development, the negative regulation of fibroblast proliferation and myoblast differentiation, and the HIF-1 signaling, AMPK signaling, and PI3K-Akt signaling pathways. Using a Venn diagram, 36 common DEGs were identified between Bos taurus, Ovis aries, and Sus scrofa. A biological pathways analysis of 36 common DEGs in Bos taurus, Ovis aries, and Sus scrofa allowed for the identification of common pathways/biological processes, such as myoblast differentiation, the regulation of muscle cell differentiation, and positive regulation of skeletal muscle fiber development, that orchestrated the development and maturation of skeletal muscle. As a result, hub genes were identified, including PPARGC1A, MYOD1, EPAS1, IGF2, CXCR4, and APOA1, in all examined species. This study provided a better understanding of the relationships between genes and their biological pathways in the skeletal muscle maturation process.